High rate and long-term cycling of silicon anodes with phosphonium-based ionic liquids as electrolytes for lithium-ion batteries - Sánchez Ramírez, Nedher (2023)
This paper describes the effects of the length of the phosphonium alkyl chain in FSI-based ionic liquids (ILs) used as an electrolyte solvent with Si electrodes in a Li/Si half-cell. The electrochemical performance of Si nanoparticles at a high rate in the synthesized triethyl-n-butylphosphonium bis(fluorosulfonyl)imide) [P2224][FSI] and triethyl-n-octylphosphonium bis(fluorosulfonyl)imide) [P2228][FSI] ILs, which also contain 1 M LiFSI, is compared with that of a common organic electrolyte using either polyacrylic acid (PAA) or polyacrylonitrile (PAN) as a binder. For the three electrolytes, the highest performance was obtained with the PAN binder, while both electrodes in ILs exhibited superior performance compared to the conventional organic electrolyte. For the Si/PAN composite electrode, after 1000 cycles at 1 A.g−1, the delithiation capacities were 1344, 550 and 136 mAh.g−1 for [P2224][FSI] in 1 M LiFSI, [P2228][FSI] in 1 M LiFSI and the commercial organic electrolyte, which corresponded to capacity retentions of 61%, 50% and 5%, respectively. Our results indicate that the chemical structure of the phosphonium cation enabled the tuning of transport properties and significantly influences the electrochemical behavior of the Si anode in the presence of LiFSI/IL as an electrolyte.